2014
DOI: 10.1038/clpt.2013.241
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Ingestion Greatly Reduces Plasma Concentrations of Nadolol in Healthy Subjects

Abstract: This study aimed to evaluate the effects of green tea on the pharmacokinetics and pharmacodynamics of the β-blocker nadolol. Ten healthy volunteers received a single oral dose of 30 mg nadolol with green tea or water after repeated consumption of green tea (700 ml/day) or water for 14 days. Catechin concentrations in green tea and plasma were determined. Green tea markedly decreased the maximum plasma concentration (C(max)) and area under the plasma concentration-time curve (AUC(0-48)) of nadolol by 85.3% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 29 publications
2
126
0
Order By: Relevance
“…Rosuvastatin has a high affinity for OATP transporters, as its K m was determined to be 2.6, 4.0, 9.8, and 2.4 mM for OATP1A2, OATP1B1, OATP1B3, and OATP2B1, respectively (Ho et al, 2006). Finally, OATP1A2 is inhibited by various flavonoids, such as naringin, apigenin, kaempferol, quercetin, and several flavonoids found in green tea Mandery et al, 2010;Roth et al, 2011;Misaka et al, 2014). Flavonoids are found in vegetables, fruits, and plants; thus, pharmacokinetic studies using flavonoids focused on intestinal interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosuvastatin has a high affinity for OATP transporters, as its K m was determined to be 2.6, 4.0, 9.8, and 2.4 mM for OATP1A2, OATP1B1, OATP1B3, and OATP2B1, respectively (Ho et al, 2006). Finally, OATP1A2 is inhibited by various flavonoids, such as naringin, apigenin, kaempferol, quercetin, and several flavonoids found in green tea Mandery et al, 2010;Roth et al, 2011;Misaka et al, 2014). Flavonoids are found in vegetables, fruits, and plants; thus, pharmacokinetic studies using flavonoids focused on intestinal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al (2007) have demonstrated that ingestion of fexofenadine and a solution of naringin decreased fexofenadine maximum plasma concentration (C max ) and the area under the plasma concentration time curve (AUC). Misaka et al (2014) have shown that green tea decreased nadolol C max and AUC. These interactions assume that OATP1A2 is an intestinal uptake transporter in the human intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Individual variation in C max and AUC of catechins after ingestion of green tea extract was observed in our pharmacokinetic study, which may be associated with the variation of P-gp activity among the subjects [26]. Recently, Misaka et al reported a significant catechin-drug interaction; green tea ingestion greatly reduced plasma concentration of β-blocker nadolol mediated by organic anion-transporter OATP1A2 [27]. The catechindrug interaction competitive antagonism or direct inhibition for transporters should be kept in mind in the clinical field.…”
Section: Pharmacokinetic Properties Of Green Tea Catechinsmentioning
confidence: 97%
“…The interaction risk of the red wine component resveratrol, marketed as a supplement with potential as a cancer chemopreventative agent, was predicted to be moderate to high if ingested at "therapeutic" doses (0.5-5 g). EGCG and ECG, two major constituents in green tea, were predicted to have high and moderate interaction risk, respectively, if consumed as tea (Misaka et al, 2014) or a supplement (Chow et al, 2001). These a C max values were limited to studies of healthy volunteers, from whose plasma the parent constituent was measured directly (i.e., independently from any of the metabolites).…”
Section: Discussionmentioning
confidence: 99%